A new species of the spider genus Plator (Trochanteriidae) from south China - Lin, Ye-Jie; Zhu, Guang-Xiang (Zootaxa, 2016)
The spider genus Plator Simon (1880) is a small and little-known group in the spider family Trochanteriidae. Species of Plator are called flat-spiders in Chinese for the extremely flat habitus (Zhu & Wang 1963). Up to now, 11 Plator species have been recorded from India, China, Korea and Japan. Six of them, P. insolens Simon (1880), P. pandeae Tikader (1969), P. pennatus Platnick (1976), P. sinicus Zhu & Wang (1963), P. yunlong Zhu et al. (2006) and P. bowo Zhu et al. (2006) are reported from China (World Spider Catalog 2016). Zhu et al. (2006) suggested two species groups for at least all Chinese Plator species, the P. insolens group and the P. pennatus group. The former can be recognized by the absence of RTA of male pedipalp, and the narrow first windings of the copulatory duct system of female epigyne and the latter, distinguished by the presence of RTA and the broad first windings of the copulatory duct system.